Environmentally Friendly Natural Coagulants in the Coagulation Process in the Rubber Industry - Achmad, Feerzet; Deviany, Deviany; Simbolon, Nur Indah; Mahendra, Lufi Eka; Suhartono, Suhartono; Suharto, Suharto (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2024)
This research evaluates the use of natural coagulants, such as soursop and Aegle marmelos (Maja), in the latex coagulation process of the GT 1 clone type, compared with chemical coagulants such as formic acid and acetic acid, to gain an understanding of the characteristics of the rubber produced. Three types of crumb rubber (SIR 3 CV, SIR 3L, and SIR 3 WF) are produced from latex, while SIR 5, SIR 10, and SIR 20 are produced from treated latex coagulum. Rubber quality criteria are explained in the Indonesian Rubber Standard (SIR 3L/3WF) SNI 06-1903-2011. The use of natural coagulants, especially soursop, and Maja, in the coagulation of GT 1 clone latex shows an influence on coagulation time, Dry Rubber Content (DRC), initial plasticity (Po), Plasticity Retention Index (PRI), ash content, dirt content, and substance content evaporate. The results showed that natural coagulants had slower coagulation times, higher DRC values ​​(especially in maja), and better PRI values ​​compared to chemical coagulants. Despite having higher ash content, dirt content, and volatile matter content, all types of coagulants meet rubber quality standards. This research provides in-depth insight into the potential and advantages of natural coagulants, especially soursop, and maja, in the environmentally friendly rubber industry. In addition, analysis of rubber characteristics, such as plasticity, resistance to heating, and content of certain components, provides a comprehensive understanding of the impact of the use of natural coagulants on rubber quality.